2020
DOI: 10.21608/ejabf.2020.119039
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic characterization and cholesterol assimilation ability of Pichia kudriavzevii isolated from the gut of the edible freshwater snail “Pila globosa”.

Abstract: High cholesterol is associated with an increased risk of developing cardiovascular disease. This may include cardiac disease, stroke, and peripheral artery disease. Diabetes and high blood pressure have also been linked to high cholesterol (Shehata et al., 2016). Probiotics, with cholesterol lowering ability, when supplemented through food can RTICLE INFO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…LC528142.1), and Saccharomyces boulardii (SB) were procured from Pathology lab, Rajiv Gandhi Institute of I.T. and Biotechnology, Bharati Vidyapeeth (Deemed to be University), Pune [23][24][25][26] .…”
Section: Materials and Methods Sample Collectionmentioning
confidence: 99%
“…LC528142.1), and Saccharomyces boulardii (SB) were procured from Pathology lab, Rajiv Gandhi Institute of I.T. and Biotechnology, Bharati Vidyapeeth (Deemed to be University), Pune [23][24][25][26] .…”
Section: Materials and Methods Sample Collectionmentioning
confidence: 99%
“…The suspension was vortexed for 2 min and incubated at 37ºC for phase separation. The decrease in absorbances of the aqueous phase was measured as per cent hydrophobicity (H %) and calculated as H %=[(A0-A)/A0]*100, where A0 and A are the absorbances of the culture in the aqueous phase before and after extraction respectively (18).…”
Section: Hydrophobicity Assaymentioning
confidence: 99%
“…In recent years, due to the food habits, people are suffering more with several cardiovascular and cerebrovascular diseases [7] associated with high cholesterol concentration. This also includes heart stroke, peripheral artery disease, diabetes, and high blood pressure [8]. Therefore, the cholesterol-lowering ability of probiotics and the associated mechanisms for cholesterol removal have received a great attention.…”
Section: Introductionmentioning
confidence: 99%
“…Reports have shown that consumption of these probiotics supplemented food can help in cholesterol reduction by producing bile salt hydrolase (BSH) enzyme and therefore, production of BSH has become a crucial selection criterion for probiotic organisms to determine their cholesterol removal ability. Besides producing BSH, probiotics also possess some inherent ability to scavenge cholesterol [8]. With reference to this, we have also screened out our isolates on the basis of BSH production and assessed their potential for cholesterol removal.…”
Section: Introductionmentioning
confidence: 99%